Penerapan Media “Teleng” Untuk Meningkatkan Hasil Belajar Sistem Gerak Manusia - Teguh Soeharto (LPMP Provinsi DKI Jakarta, 2021)
Minimum completeness criteria for the movement system in humans at SMP Negeri 3 Babelan in 2020 shows learning outcomes. It was caused by the limited media that can be used to learn concepts. Media